(untitled) (Eurasian Scientific Herald, 2023)
The topic reflected in the article is devoted to the relationship between husband and wife The topic reflected in the article is devoted to the relationship between husband and wife. The article is intended for psychologists-researchers, employees working in the field of spirituality and enlightenment